Diffusion-limited association of disordered protein by non-native electrostatic interactions. Issue 1 (December 2018) - Kim, Jae-Yeol; Meng, Fanjie; Yoo, Janghyun; Chung, Hoi
Abstract Intrinsically disordered proteins (IDPs) usually fold during binding to target proteins. In contrast to interactions between folded proteins, this additional folding step makes the binding process more complex. Understanding the mechanism of coupled binding and folding of IDPs requires analysis of binding pathways that involve formation of the transient complex (TC). However, experimental characterization of TC is challenging because it only appears for a very brief period during binding. Here, we use single-molecule fluorescence spectroscopy to investigate the mechanism of diffusion-limited association of an IDP. A large enhancement of the association rate is observed due to the stabilization of TC by non-native electrostatic interactions. Moreover, photon-by-photon analysis reveals that the lifetime of TC for IDP binding is at least two orders of magnitude longer than that for binding of two folded proteins. This result suggests the long lifetime of TC is generally required for folding of IDPs during binding processes. Intrinsically disordered proteins (IDPs) usually fold during binding to target proteins which involves the formation of a transient complex (TC). Here authors use single-molecule FRET to show that the lifetime of TC for IDP binding is very long due to the stabilization by non-native electrostatic interactions, which makes fast association possible.